Extraocular Muscle Repair and Regeneration - Verma, Mayank (Curr Ophthalmol Rep, 2017)
PURPOSE OF REVIEW: The goal of this review is to summarize the unique regenerative milieu within mature mammalian extraocular muscles (EOMs). This will aid in understanding disease propensity for and sparing of EOMs in skeletal muscle diseases as well as the recalcitrance of the EOM to injury. RECENT FINDINGS: The EOMs continually remodel throughout life and contain an extremely enriched number of myogenic precursor cells that differ in number and functional characteristics from those in limb skeletal muscle. The EOMs also contain a large population of Pitx2-positive myogenic precursor cells that provide the EOMs with many of their unusual biological characteristics, such as myofiber remodeling and skeletal muscle disease sparing. This environment provides for rapid and efficient remodeling and regeneration after various types of injury. In addition, the EOMs show a remarkable ability to respond to perturbations of single muscles with coordinated changes in the other EOMs that move in the same plane. SUMMARY: These data will inform Ophthalmologists as they work toward developing new treatments for eye movement disorders, new approaches for repair after nerve or direct EOMs injury, as well as suggest potential explanations for the unusual disease propensity and disease sparing characteristics of human EOM.